Liquefaction Potential based on Earthquake History in Sanana Region, Sula Island Regency, North Maluku, Indonesia - Pajrin, Ulfia Sari; Zakaria, Zufialdi; Sophian, Raden Irvan; Khoirullah, Nur; Mubarak, Aziez; Basuki, Jodi Prakoso (Journal of Geological Sciences and Applied Geology, 2019)
Sula Islands is a region in Maluku Province that is very vulnerable to earthquakes because it is located on an active seismic line. One of the disasters that often accompanies earthquakes is liquefaction. Sandy soil in a saturated condition will lose its strength when an earthquake occurs, thus endangering the building above it. The aim of the study was to determine seismicity and estimate the liquefaction potential of the earthquake history and CPT test in the Sanana region and its surroundings. The method in this study uses a "simplified procedure" method for evaluating liquefaction resistance of soils. 2 main parameters were sought in this study, CSR obtained based on tectonic conditions and a history of seismicity and CRR obtained from the results of CPT testing. The results showed that seismicity in the Sanana region was sourced from Sula-Sorong active fault activity with a history of the greatest magnitude of 8.1 and 7.7. As for the calculation results from CPT data, the Sanana area has the potential for liquefaction of sand medium material at a depth of 5-12 m for earthquakes with magnitude 7.5 and 4 -12 m in magnitude 7.7 and 8.1. The potential for liquefaction in this area is caused by the type of saturated medium sand material and this location which is close to the active fault activity of Sula-Sorong. Therefore, it is necessary to evaluate the potential for liquefaction in planning, building and developing infrastructure in earthquake-prone areas so that disasters of liquefaction can be prevented.